Meningkatkan Hasil Belajar Siswa dalam Membuat Gambar Dekoratif Pada Pembelajaran Seni Budaya Dan Prakarya Dengan Menggunakan Media Kolase - Ernasari; Rifki Arif Nugraha; Yeni Sulaeman; Ade Farid (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
ABSTRACT   Ernasari. Improving Student Learning Outcomes in Making Decorative Images in Cultural Arts and Crafts Learning Using Collage Media for Grade 3 Students at SDN Kawoyang 1. Thesis for Bachelor of Elementary School Teacher Education Study Program (PGSD) Teacher Training and Education College (STKIP) Syekh Manshur Pandeglang. The method used in this research is collaborative classroom action research (CAR). Researchers collaborate with teachers to plan, identify, observe, and carry out the actions that have been designed. The research design used was a spiral system class action research with the Hopkins and John Eliot models which began with preliminary actions then continued with planning, action, observation, and reflection. The research was conducted in 2 cycles. The research was carried out at SDN Kawoyang 1, Kawoyang Village, Carita District, Pandeglang Regency, Sempel selected in this study were 33 grade 3 students consisting of 17 boys and 16 girls. In this study there were several stages carried out from pre-cycle research, cycle I, and cycle II The results of this study note that in the pre-cycle conditions, students who completed learning were 12 students, around 36% of 33 students with a class average of 52.12, after carrying out activities in cycle I, the number of students who completed learning became 21 students from 33 students or about 63% with an average value of 71.36. In cycle II, it is known that there are 29 students out of 33 students who have successfully completed their studies, obtaining an average score of 77.57, with a completeness percentage of 87% and can be said to be successful. The increase in student learning outcomes in the subject of Cultural Arts and Crafts on decorative drawing material is motivated by the use of effective and fun learning media so that it can motivate students' interest in learning to be even better. The learning media used is collage learning media. Keywords: Learning Outcomes, Learning Arts and Crafts, Decorative Drawing Materials, Collage Media.